Perencanaan dinding penahan tanah untuk menanggulangi kelongsoran pada kompleks peternakan ayam di Kecamatan Kandangan, Kediri, Jawa Timur - K. Wardani, Mila; T. Nuciferani, Felicia; F.N. Aulady, Mohamad (Borneo Engineering : Jurnal Teknik Sipil, 2018)
Landslide one of the natural disasters that caused many victims. Therefore, the landslide need a construction that can withstand landslide force. This study aims to plan retaining walls to prevent landslides in the farm area in Kandangan Subdistrict, Kediri Regency. The method used is to use slide analysis which is used to plan the retaining wall. In addition the planning of soil containment walls u ses several methods as a comparison. The results of this study indicate that the planning of ordinary soil retaining walls is still not enough to overcome slides. The minimum SF value that meets the safe limit of landslide prevention is 1.541 in the combination of 1/3 H terracing and the number of gabions as many as 7 with a total height of 2- 3 m .